2013
DOI: 10.7883/yoken.66.391
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Mannose-Binding Lectin in Intrauterine Transmission of Hepatitis B Virus

Abstract: SUMMARY: Intrauterine transmission of hepatitis B virus (HBV) is the main cause of the high prevalence of HBV in endemic areas; however, the mechanisms underlying intrauterine transmission of HBV remain unknown. To explore the role of mannose-binding lectin (MBL), a pattern recognition molecule of the innate immune system, in intrauterine transmission of HBV, we determined MBL levels using an enzyme-linked immunosorbent assay (ELISA) in cord serum of 7 intrauterine-infected neonates and 30 non-infected neonate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…For example, mannose-binding lectin can combine with HBV directly by identifying the N-acetyl glucosamine and mannose sugar structure on the envelope of HBV, resulting in viral clearance (2,15). In addition, research suggests that the surface antigen entire deglycosylation of virus particles could affect the stability of the protein, change its space structure, and even cause the virion to lose its immunogenicity (10).…”
Section: Discussionmentioning
confidence: 99%
“…For example, mannose-binding lectin can combine with HBV directly by identifying the N-acetyl glucosamine and mannose sugar structure on the envelope of HBV, resulting in viral clearance (2,15). In addition, research suggests that the surface antigen entire deglycosylation of virus particles could affect the stability of the protein, change its space structure, and even cause the virion to lose its immunogenicity (10).…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that MBL polymorphisms that confer low levels of MBL are correlated with poor prognoses such as HBV persistence [Thio et al, ], disease progression [Yuen et al, ; Song le et al, ; Chong et al, ]. It was shown that low fetal MBL is associated with intrauterine infection of HBV [Wu et al, ]. In this study, it was found HBV in vitro up‐regulated MBL expression of trophoblast but the expression of placental MBL did not significantly differ among non‐infected, infected, and control groups.…”
Section: Discussionmentioning
confidence: 59%
“…With a mother to child transmission rate of HBV in the region of 5 -10%, intra-uterine transmission of HBV may be related to a failure of HBV infected mothers to stimulate an increase in foetal MBL levels to combat the virus. It has been shown that non-infected neonates of HBV mothers have an induced increase in MBL levels conferring protection whilst neonates born with HBV have a significantly lower level of MBL [37].…”
Section: Mbl and Hepatitis B Virus (Hbv)mentioning
confidence: 99%